Ação de detergentes e desinfetantes em biofilme tradicional e buildup no modelo MBEC - Luciano, Cristiana da Costa (2016)
INTRODUCTION: Flexible Gastrointestinal Endoscopes (FGE) are used for diagnostic and therapeutic procedures, classified as semicritical health products (HP), requiring High-Level Disinfection (HLD) processing among users. The FGE designs are complex, making it difficult to process and favor the occurrence of faults that contribute to the accumulation of organic matter on the surface of the internal channels of the endoscopes, contributing to the formation of the biofilm. OBJECTIVE: To develop a Biofilm Buildup (BBF) accumulation model, based on repeated exposure of test soil containing Entercoccus faecalis and Pseudomonas aeruginosa by means of repeated cycles of fixation and to evaluate the ability of detergents and disinfectants to destroy and remove bacteria in the Traditional Biofilm (TBF) and Buildup. MATERIALS AND METHODS: TBF was developed in MBEC ™ peg, without hydroxyapatite, and BBF, with hydroxyapatite, over a period of eight days. For the development of both biofilms, E. faecalis and P. aeruginosa, containing 8 log10, colony forming units per cubic centimeters (CFU/cm2) were used. Prolystica Enzymatic (D1), Prolystica Neutral (D2), Neodisher (D3) and Endozime (D4) were tested alone and in combination with Glutaraldehyde (GLUT), Orthophthaldehyde (OPA) and Hydrogen Peroxide Accelerator (APH) to determine if both biofilms could be removed. The removal of the traditional biofilm and buidulp, using viable bacteria count, quantification of protein and carbohydrates and by means of scanning electron microscopy (SEM) was evaluated. RESULTS: After eight days of BBF development, 6.14 log10 CFU/cm2 of E. faecalis and 7.71 log10 CFU/cm2 of P. aeruginosa were reached. None of the detergents and disinfectants have been able to remove the traditional biofilms and buildup or reduce the level of bacteria. The combination of detergents and disinfectants tested in BBF provided a reduction of 3 to 5 log10 in viable bacteria, but no combination could provide the expected reduction of l log10. Only enzyme Prolystica and Endozime removed both E. faecalis (3.90 log10 colony forming units per milliliter (CFU/mL)) and P. aeruginosa (3.96 log10 CFU/mL) in suspension bacteria. None of the detergents tested removed > 1 log10 CFU/cm2 from the bacteria within the traditional biofilm. No combination of high-level disinfectant and detergent reduced the level of both E. faecalis and P. aeruginosa from the traditional biofilm interior (3 to 5 log10 CFU/cm2). Although the combination of Endozyme and Glutaraldehyde reduced 6 log10, it did not eliminate both bacteria in the traditional biofilm. CONCLUSION: Data indicate that if TBF and BBF accumulate in the EGF channels during repeated processing cycles, neither detergents nor high level disinfectants will provide the expected level of bacterial removal or destruction. Future research using the buildup model can help develop new cleaning and disinfection methods that can prevent or eliminate the BBF within the endoscope channels.